Infection Control Programs Related to Healthcare: evaluation of structure and process indicators (Research, Society and Development, 2022)
This study aims to evaluate the Health Care-Related Infection Control Programs in eight municipal hospitals in São Luís - MA. This is a descriptive and exploratory, quantitative study, carried out in 2020, through the application of an instrument consisting of four clinical indicators, two of which are structural (Technical-Operational Structure of the Health Care-Related Infection Control Program and Guidelines Operational Control and Prevention of Infection Related to Health Care) and two of processes (Epidemiological Surveillance System for Infection Related to Health Care and Control and Prevention Activities Related to Health Care). The indicator that assesses the operational guidelines had the highest average of compliance (70.5%), followed by the indicator that assesses the technical-operational structure (68.8%). The structure indicators showed lower compliance (37.5%) in the components meetings with leaders and managers, exclusive physical space for their activities and standardization of germicidal and antiseptic solutions. Process indicators had lower rates in the components related to reporting on hospital infections (37.5%) and carrying out control and prevention activities in the nutrition and diet sector (12.5%). The services evaluated show better performance in the structure indicators and show fragility regarding essential activities for the prevention of hospital infections, such as carrying out epidemiological surveillance and developing prevention and control strategies for these infections in different sectors of the hospital.